Determinants pedologiques, climatiques et socioeconomiques sur le choix des agriculteurs de la Casamance et du Senegal oriental a cultiver le riz de plateau - Julien Diatta (2023)
This paper investigates the determinants that may influence upland rice cultivation in Casamance and eastern Senegal. The main objective is to understand the climatic, pedological and socio-economic factors that explain the motivation of farmers in this southern zone of Senegal to grow upland rice. Various types of data were mobilized to highlight this study. These include climatic data (rainfall, relative humidity, maximum temperatures, minimum temperatures, radiation), soil data (hydrogen potential, phosphorus, potassium, nitrogen, sodium, iron, cation exchange capacity, carbon content, sand, silt, clay) and socio-economic data (social capital, land ownership, human capital, physical capital, choice of farming activities, geographical location) were collected by SODAGRI, ISRA BAME and CIRAD (funded by CRP RICE), and by the author for study validation purposes. Complementary data from NASA were also used. Various methods were used: Multiple Factor Analysis (MFA) and a clustering analysis (K- means) on the principal components of the MFA applied to climatic and soil data; Logit modelling applied to socio-economic variables, and mapping for spatial analyses. The software used was Excel, STATA 17, R, R-Studio and ArcGis Pro. The results obtained indicate that the factors that could influence farmers in Casamance and eastern Senegal to grow upland rice are geographical location, soil factor, human capital, physical capital, livelihood activities, land tenure and soil typology.